Bank Privatization and Productivity : Evidence for Brazil - Nakane, Márcio I. (World Bank, Washington, DC, 2012)
Over the past decade, the Brazilian banking industry has undergone major and deep transformations with several privatizations of state-owned banks, mergers and acquisitions, closing down of troubled banks, entry by foreign banks, and so on. The purpose of this paper is to evaluate the impacts of these changes in banking on total factor productivity. The authors first obtain measures of bank level productivity by employing the techniques due to Levinsohn and Petrin (2003). They then relate such measures to a set of bank characteristics. Their main results indicate that state-owned banks are less productive than their private peers, and that privatization has increased productivity.